Factors influencing wettability and surface/interface mechanics of plant surfaces: a review - Tie, Jinxin; Gao, Mengyuan; Huang, Yulin; Li, Kecheng; Wang, Hui (Frontiers in Materials, 2023)
A wide variety of abundant plant leaves exist in nature, and the wettability of their surfaces is formed to adapt to diverse external environments. In this paper we will focus on the factors influencing the wettability of various plant leaves prevalent in nature. And we hope to investigate the interfacial problems of plants from a mechanical point of view. It is found that there are many factors affecting the surface wettability of leaves, such as chemical composition, surface microstructures, hierarchical structures, and growth age. Different influencing factors have different contributions to the change of surface wettability. The surface wax composition influences the surface wettability from a chemical point of view while the hierarchical structure consisting of nanostructures and micron structures also influences the wettability from a structural point of view. Also as the growth age of the plant increases, there is a combined effect on the chemical composition and microstructure of the leaves.Then we discuss the surface/interface mechanics of droplets on various plant leaves and analyze the wetting properties of droplets on different substrates. Finally, we hope that the surface/interface mechanics of plant leaves may be systematically utilized in the future for the preparation of multifunctional biomimetic materials, realizing the crossover of chemistry, biology, mechanics, and other materials science fields.